Pengaruh Word Of Mouth, Lokasi, dan Harga terhadap Keputusan Pembelian di Toko Kopi Epidemi Jombang - Ivan Adi Putra Ardhana; Taufik Akbar; Karari Budi Prasasti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to explain and examine the influence of Word of Mouth, location, and price on purchase decisions of consumers at Toko Kopi Epidemi Jombang. A quantitative method with a causal research approach was applied. Data were collected through questionnaires distributed to 80 respondents. The analysis techniques included validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression, t-test (partial), F-test (simultaneous), and the coefficient of determination (R²), using SPSS version 26. The results showed that partially, tabel had a significant effect on purchase decisions with a significance value of 0.000 < 0.05 and a t-value of 4.483 > t-table 1.995. The location variable did not have a significant effect on purchase decisions, with a significance value of 0.640 > 0.05 and a t-value of 0.470 < t-table 1.995. Meanwhile, price had a significant effect on purchase decisions with a significance value of 0.000 < 0.05 and a t-value of 2.181 > t-table 1.995. Simultaneously, Word Of Mouth, location, and price had a significant effect on purchase decisions with a significance value of 0.000 < 0.05 and an F-value of 27.623 > F-table 2.70. The coefficient of determination (R²) indicated that the three variables collectively explained 52.2% of the variance in purchase decisions, while the remaining 47.8% was influenced by other factors not examined in this study.